2008
DOI: 10.3982/ecta7673
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Keep Their Promises? An Experimental Test of Two Explanations

Abstract: Numerous psychological and economic experiments have shown that the exchange of promises greatly enhances cooperative behavior in experimental games. This paper seeks to test two theories to explain this effect. The first posits that individuals have a preference for keeping their word. The second assumes that people dislike letting down others' payoff expectations. According to the latter account, promises affect behavior only indirectly, because they lead to changes in the payoff expectations attributed to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(62 citation statements)
references
References 13 publications
(22 reference statements)
2
41
0
1
Order By: Relevance
“…For example, Charness and Dufwenberg (2006) classified 57 % of their messages from B in the (5, 5) treatment as promises; Vanberg (2008) classified 85 % of the messages as promises in No Switch and 77 % of the messages as promises in Switch. Using the same procedure as we do, Houser and Xiao (2010) found that 74 % of the B messages from Charness and Dufwenberg (2006) (5,5) experiment were categorized as promises by the evaluators in their weak promise treatment.…”
mentioning
confidence: 99%
“…For example, Charness and Dufwenberg (2006) classified 57 % of their messages from B in the (5, 5) treatment as promises; Vanberg (2008) classified 85 % of the messages as promises in No Switch and 77 % of the messages as promises in Switch. Using the same procedure as we do, Houser and Xiao (2010) found that 74 % of the B messages from Charness and Dufwenberg (2006) (5,5) experiment were categorized as promises by the evaluators in their weak promise treatment.…”
mentioning
confidence: 99%
“…The first possible influence mechanism is the internalized norm mechanism. The substance of this mechanism is that making promises activates promisors' internalized norm of promise-keeping and a desire to comply with the norm of promise-keeping per se motivates individuals to keep their word and improve their level of cooperation (Kerr et al, 1997;Ellingsen and Johannesson, 2004;Vanberg, 2008;Ellingsen et al, 2010;Kawagoe and Narita, 2014;Krupka et al, 2016, etc.). That is, individuals keep their promises due to self-consciousness 1 .…”
Section: Introductionmentioning
confidence: 99%
“…One is the homogeneous aversion to lying model suggested by Ellingsen and Johannesson (2004), Miettinen and Suetens (2008), and Vanberg (2008), where the model assumes that people incur a similar fixed cost in their utilities when caught lying; the other is the heterogeneous cost of lying model, where different people might incur different costs while caught lying (e.g., Gibson et al (2013)). …”
Section: Intrinsic Preference For Honesty Modelsmentioning
confidence: 99%
“…The literature further suggests that communication, particularly informal contract/commitment, is crucial for facilitating cooperation and improving efficiency. (see, for example Charness and Dufwenberg, 2006;Charness et al, 2012Charness and Dufwenberg, 2011;Miettinen and Suetens, 2008;Vanberg, 2008;Ellingsen and Johannesson, 2004;Kerr and Kaufman-Gilliland, 1994;Loomis, 1959;Sally, 1995). By the same token, the literature indicates that people not only strive to keep their promises, but are also averse to breaking informal contracts and lying to others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation